Crystal structure, Hirshfeld surface and reactivity of novel ligand-LAT1 derived from dehydroacetic acid: intermolecular interactions with SARS-Cov-2/main protease. Issue 1 (29th June 2021) - Denni, Imene; Ait Ramdane-Terbouche, Chafia; Terbouche, Achour; Abdeldjebar, Hasnia; Lakhdari, Houria; Ait-Ramdane, Khaled; Bachari, Khaldoun; Roisnel, Thierry; Hauchard, Didier; Ghemmit-Doulache, Naima
Abstract: The crystals of new ligand, namely (3 E )-6-methyl-3-{1-[(pyridin-3-ylmethyl) amino] ethylene}-2 H -pyran-2, 4(3 H )-dione) (LAT1 ), were synthesized using the evaporation solution technique. Single-crystal X-ray diffraction and physico-chemical characterization (ATR, proton and carbon-13 NMR and UV-Visible) of LAT1 were reported. In addition, Hirshfeld surface analysis (HSA) of the solid compound, structure optimization, Mulliken and NBO charges, global indices of reactivity, local reactivity descriptors and molecular electrostatic potential (MEP) of the ligand were investigated theoretically. XRD analysis showed that LAT1 crystallizes in the triclinic space group P-1 and the structure was stabilized through hydrogen bonds. HAS revealed that H…H (46.5%) and O…H (25.7%) contacts are in control of crystal stacking. The energy gap (4.679 eV) and reactivity descriptors indicate the stability of LAT1 . The Mulliken and NBO charges showed that the protons have a positive charge and the heteroatoms exhibit negative charges. The Fukui function and MEP study revealed that the heteroatoms are the most reactive sites for an electophilic attack on the ligand. Molecular docking simulation shows that the significant binding affinity of LAT1 with SARS-CoV-2/Mpro is due to the formation of high number of hydrogen bonds.